2020
DOI: 10.1007/s42452-020-2594-6
|View full text |Cite
|
Sign up to set email alerts
|

Monazite chemistry and its distribution along the coast of Neendakara–Kayamkulam belt, Kerala, India

Abstract: The beach sands along the coasts of India contain large reserves of strategic minerals like ilmenite, monazite, zircon, etc. Monazite mineral is primarily used as an ore for extracting rare earths particularly cerium and lanthanum. In the present study, the chemistry and distribution of monazite found in the beach sands of Neendakara-Kayamkulam belt in Kerala, south India, is studied using advanced techniques and standardized methods. Beach sediments were collected and analyzed for the texture, and mineralogy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…The micrographs of RM revealed that the particles are slightly spherical and elongated to sub-rounded in shape. Moreover, physical fractured features and irregular shaped particles are also observed on the surface of particles of MM-Lab, MS-Lab, MM-PP and MS-PP, respectively [10]. These morphological features clearly reveal that the mechanical process of milling and sieving gave an impact on the surface of monazite particles.…”
Section: Effect Of Particle Size Analysis To the Morphology And Eleme...mentioning
confidence: 76%
“…The micrographs of RM revealed that the particles are slightly spherical and elongated to sub-rounded in shape. Moreover, physical fractured features and irregular shaped particles are also observed on the surface of particles of MM-Lab, MS-Lab, MM-PP and MS-PP, respectively [10]. These morphological features clearly reveal that the mechanical process of milling and sieving gave an impact on the surface of monazite particles.…”
Section: Effect Of Particle Size Analysis To the Morphology And Eleme...mentioning
confidence: 76%
“…The bulk chemical composition was studied using Pan Analytical Epsilon 3 ED-XRF instrument having Omnion software. ED-XRF technique is used to determine the elemental composition, especially the major oxides range from percentage to ppm level in minerals such as monazite (Anitha et al 2020), sillimanite (Jin et al 2016), garnet, and ilmenite (Sajimol et al 2017). The SEM micrographs were taken using JEOL make model JSM5600 LV.…”
Section: Methodsmentioning
confidence: 99%
“…Many modern and paleo-placer deposits occur bordering the Indian Ocean, mainly in coastal and shallow marine environments (Herath 1980 ; Wickremeratne 1986 ; Mallik et al 1987 ; Anitha et al 2020 ). Coastal stretches towards the Central Indian Ocean show the dominant provenance of their HMs.…”
Section: Global Distribution Of Hmsmentioning
confidence: 99%